Tracing a Memetic Journey: From South American Death Flights to Free Helicopter Ride Memes - Martinez Pandiani, Delfina Sol (AoIR Selected Papers of Internet Research, 2026)
This paper examines how a traumatic South American symbol—the death flights used by Southern Cone dictatorships in the 1970s–1980s—has been repurposed as a viral meme. Over the past decade, this symbol of extrajudicial execution resurfaced as the “free helicopter rides” meme on platforms such as 4chan, circulating as coded alt-right rhetoric. This transformation ruptures historical memory, as a symbol of state terror is appropriated, recast through U.S. political antagonisms, and reshaped within Global North digital cultures. While research has mapped alt-right speech and meme dynamics, little examines how Global South symbols are decontextualized, commodified, and re-exported.Using a mixed-methods approach—combining computational analysis of 2013–2023 /pol/ posts, qualitative meme tracing, and cross-platform digital ethnography—the study reconstructs six stages in the meme’s trajectory: from disappearance regimes to U.S. alt-right adoption, commodification via global marketplaces, and reentry into South America as consumer products. The findings show how memetic far-right cultures, together with platform infrastructures, detach and monetize historical trauma, producing memetic trauma extractivism in which Global North actors recode, commodify, and resell symbols of Global South violence. The analysis underscores the need for interdisciplinary, data-driven research on how digital culture circulates and commercializes traumatic memory, reshaping global relations of meaning and power.